Revisitando a proveniência do cobre usado em Leceia: DOI: https://doi.org/10.5281/zenodo.7920135 - Valério, Pedro; Cardoso, João Luís; Soares, António M. Monge (Estudos Arqueológicos de Oeiras, 2023)
The work presents a revaluation of a pioneer research about the copper provenance in the Chalcolithic settlement of Leceia (Oeiras, Portugal) considering theoretical developments in the application of lead isotope analyses, in addition to the recent publication of the large IBERLID database including copper ores from Iberian Peninsula. Therefore, the lead isotope ratios of 14 copper artefacts and copper prills from Leceia were compared with the signatures of those copper ores and the similarity between metal and probable source signatures was assessed with the calculation of Euclidean Distances (using 206Pb/ 204Pb, 207Pb/204Pb and 208Pb/204Pb). Considering the present knowledge, the results confirmed that copper deposits in the South Portuguese Zone and the Ossa‑Morena Zone can in fact be the source of some of the copper used in that Chalcolithic settlement. However, new evidence also indicates an important origin of copper, not in mines from southern Portugal, but perhaps in deposits located farther away in Los Pedroches batholith at the Central Iberian Zone.